LIMBIC ENCEPHALITIS VERSUS LESARGHUS– COMPARING THE SIMILARITIES - Dr. Md. Ibran; Dr. Md. Tanwir Alam; Dr. Shahraf Naaz; Dr. Md. Raghib Ahmad Naz (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Limbic encephalitis (LE), described in by Brierley et al., (1960) as “it is a rare neurological clinical entity of subacute course that causes neuropsychiatric symptoms where inflammation affects the limbic system, a part of the brain involved in emotions, memory, and behaviour.” It's often associated with autoimmune responses or can be paraneoplastic (related to cancer). The condition can present with a variety of symptoms, including memory problems, confusion, seizures, and psychiatric manifestations. In addition to the usual symptoms of encephalitis such as altered consciousness, fever, and focal neurological deficits, limbic encephalitis can present with neuropsychiatric manifestations and seizures. Autoimmune encephalitis is the supraordinate term to LE; this term is often used as a comprise for non-paraneoplastic and paraneoplastic forms. LE can be short-lived and subside quickly upon immunologic therapy; in other instances, it may transgress into epilepsy.There is a disease mentioned in Unani literature, by the name Lesarghus, classified under sarsam which has signs and symptoms nearly similar to Limbic Encephalitis described in modern medicine. Lesarghus is a chronic condition caused due to ghair tabai Balgham (abnormal phlegm). Continuous fever, Yawning, Loss of memory, continuous sleepy feeling, Lymphadenopathy, Headache, Seizures/spasms & vomiting etc., are usual symptoms of Lesarghus. The purpose of this review is to describe the similarities between Lesarghus & Limbic encephalitis.